PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA POSTER TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS III UPT SPF SD INPRES PARANG KOTA MAKASSAR - Ramadhani, Afifah; Karmila Sari Achmad, Widya; Salam, Rosdiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Project Based Learning (PjBL) model assisted by poster media on students’ learning outcomes in IPAS for third grade students at UPT SPF SD Inpres Parang, Makassar City. This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 27 students, including 13 students in the experimental class and 14 students in the control class. Data were collected through pretests and posttests in the form of multiple-choice questions. The data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics version 25. The results showed that the mean posttest score of the experimental class was 84.10, categorized as very good, while the control class obtained a mean score of 70.00, categorized as good. The Independent Sample t-Test showed a significance value (Sig. 2-tailed) of 0.023 at the 0.05 significance level. The value indicated the effect of the implementation of the Project Based Learning (PjBL) model assisted by poster media on the IPAS learning outcomes of third grade students at UPT SPF SD Inpres Parang, Makassar City. Based on the results of the study, teachers are recommended to use the Project Based Learning (PjBL) model assisted by poster media as an alternative learning model in IPAS instruction.